STRATEGI PEMBENTUKAN KETERAMPILAN CRITICAL THINKING PLUS MAHASISWA UNIVERSITAS GADJAH MADA BERBASIS PROJEK KEWARGANEGARAAN - Purwantiningsih, Ary; Riyanti, Dwi; Irfani, Sabit (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The aim of this research is to analyze the critical thinking skills of Gadjah Mada University students through a citizenship project-based learning model.The research method used is descriptive research with a qualitative approach. The techniques used to collect data use observation, interviews, and document and archive searches.The results of this research show the citizenship learning strategy implemented at Gadjah Mada University using citizenship projects. Students are directed to be able to analyze citizenship problems in social, national and state life and find solutions in a creative idea outlined in a project. Citizenship project-based learning strategies can improve creativity skills, think critically, search for information and utilize ideas and information related to citizenship issues. As a follow-up to this citizenship project, students can invite various levels of society to participate in implementing the ideas contained in a citizenship project.